A Systematic Literature Review of Spine Neurostimulation Therapies for the Treatment of Pain. Issue 7 (29th May 2020) - Deer, Timothy R; Grider, Jay S; Lamer, Tim J; Pope, Jason E; Falowski, Steven; Hunter, Corey W; Provenzano, David A; Slavin, Konstantin V; Russo, Marc; Carayannopoulos, Alexios; Shah, Jay M; Harned, Michael E; et al.
Abstract: Objective: To conduct a systematic literature review of spinal cord stimulation (SCS) for pain. Design: Grade the evidence for SCS. Methods: An international, interdisciplinary work group conducted literature searches, reviewed abstracts, and selected studies for grading. Inclusion/exclusion criteria included randomized controlled trials (RCTs) of patients with intractable pain of greater than one year's duration. Full studies were graded by two independent reviewers. Excluded studies were retrospective, had small numbers of subjects, or existed only as abstracts. Studies were graded using the modified Interventional Pain Management Techniques–Quality Appraisal of Reliability and Risk of Bias Assessment, the Cochrane Collaborations Risk of Bias assessment, and the US Preventative Services Task Force level-of-evidence criteria. Results: SCS has Level 1 evidence (strong) for axial back/lumbar radiculopathy or neuralgia (five high-quality RCTs) and complex regional pain syndrome (one high-quality RCT). Conclusions: High-level evidence supports SCS for treating chronic pain and complex regional pain syndrome. For patients with failed back surgery syndrome, SCS was more effective than reoperation or medical management. New stimulation waveforms and frequencies may provide a greater likelihood of pain relief compared with conventional SCS for patients with axial back pain, with or without radicular pain.